Tool for the control management of electric and magnetic fields of electrical companies - Arnera, Patricia Liliana (2008)
The use of electricity involves a wide range of activities that, because of its diversity, characteristics and relative importance causes different environmental impacts during the extraction, processing, transport and consuming activities. It is the role of the government to elaborate the rules for the incorporation of environmental aspects in the different segments of the market for different electrical energy sources and in all the stages of the process, from the initial evaluation to the construction and exploitation phases. Among the environmental key aspects to considerate, are the electric and magnetic fields, in which society has taken special interest as they are believed to be involved in health hazard. The faculties of the regulatory authority is dictate regulations and technique procedures to be fulfilled by the agents, and check their compliance. In the course of time since the mentioned obligations, the authority has gathered information regarding electric and magnetic fields that includes those planned in the Companies Environmental Planning and those obtained ad-hoc in the role of controller. In order to systematize this information, a data base has been designed considering different types of electric installations, the company which they belong to, equipment used in the measurements, representative layouts with measure points and profiles of the electric and magnetic fields that were obtained.